Enhancing Speaking Skills: The Impact of the Audio-Lingual Method on Eighth-Grade Students - Hermansyah, Sam; Mothe, Prashant (Lingua : Journal of Linguistics and Language, 2025)
This research explores the impact of the Audio-Lingual Method (ALM) on enhancing the speaking skills of eighth-grade students at SMP Negeri 1 Baranti. The study aimed to address common speaking difficulties, such as pronunciation issues, limited vocabulary, and lack of confidence, through the application of ALM techniques. A pre-experimental design was employed, with a sample of 23 students from class VIII.1, who underwent both pre-test and post-test assessments. The results indicated a significant improvement in students' speaking skills, particularly in areas of accuracy, fluency, and comprehensibility, following the implementation of the ALM over a four-week period. Statistical analysis revealed that the post-test scores were significantly higher than the pre-test scores, confirming the effectiveness of the Audio-Lingual Method in improving English speaking proficiency. The study concludes that the ALM is an effective teaching method for fostering students' speaking skills, enhancing their confidence, and encouraging active participation in the learning process.